Antioxidant and Anti-Inflammatory Potential of Cymbopogon nardus Ethanol Extract on 3T3-L1 Cells - Rohmawaty E; Wiraswati HL; Zahra TA; Amalina SN; Ramadhanti J; Rosdianto AM; Laelalugina A; Nasution GTD; Kamisah Y (Journal of Inflammation Research)
Enny Rohmawaty,1 Hesti Lina Wiraswati,1 Tamara Aliya Zahra,2 Shabrina Nur Amalina,2 Julia Ramadhanti,1 Aziiz Mardanarian Rosdianto,1 Amila Laelalugina,3 Gita Tiara Dewi Nasution,1 Yusof Kamisah4 1Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Bandung, 40161, Indonesia; 2Undergraduate Program Medical Doctor, Faculty of Medicine, Universitas Padjadjaran, Bandung, 40161, Indonesia; 3Oncology and Stem Cell Working Group, Universitas Padjadjaran, Bandung, 40161, Indonesia; 4Department of Pharmacology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Kuala Lumpur, 53000, MalaysiaCorrespondence: Enny Rohmawaty, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jl. Ir. Soekarno KM. 21, Jatinangor, Sumedang, West Java, 45363, Indonesia, Email e.rohmawaty@unpad.ac.idPurpose: Cymbopogon nardus (L). Rendle has traditionally been recognized for its medicinal properties. Recent studies have suggested that its bioactive constituents possess antioxidant and anti-inflammatory properties. However, there is limited scientific evidence of its cellular effects. Given that the pathogenesis of many diseases involves oxidative stress and inflammation, this study aimed to evaluate the potential antioxidant and anti-inflammatory effects of the plant extracts in 3T3-L1 cells.Methods: Phytochemical screening of C. nardus extracts was performed to identify bioactive compounds. Antioxidant activity of the extract was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and superoxide dismutase (SOD) assays. Toxicity was evaluated using the MTT assay. Additionally, the effects of the extract on the gene expression of hypoxia-inducible factor 1α (HIF-1α) in menadione-induced 3T3-L1 cells, as well as interleukin-6 (IL-6) and cyclooxygenase-2 (COX-2) in lipopolysaccharide (LPS)-induced 3T3-L1 cells, were investigated.Results: Phytochemical screening revealed the presence of phenolics, tannins, alkaloids, and flavonoids in the ethanolic extracts. The extract demonstrated antioxidant activity, with IC50 values of 178.06 ppm for DPPH and 220 ppm for SOD. It did not affect the viability of 3T3-L1 cells at concentrations of up to 500 ppm. At 100 ppm, the extract increased cell viability (p< 0.05) and reduced HIF-1α expression in the menadione-treated cells (p< 0.05). Additionally, it decreased the expression of IL-6 and COX-2 in LPS-induced cells (p< 0.05).Conclusion: The ethanol extract of C. nardus demonstrated promising potential as an antioxidant and anti-inflammatory agent in 3T3-L1 cells. Further analysis is recommended to confirm the potential.Keywords: ROS, IL-6, COX-2, HIF-1α, menadione, lipopolysaccharide